2020
DOI: 10.1016/j.molcel.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

N6-Deoxyadenosine Methylation in Mammalian Mitochondrial DNA

Abstract: Highlights d N 6 -methyldeoxyadenosine (6mA) is enriched in human mitochondria DNA (mtDNA) d METTL4 can mediate mammalian mtDNA 6mA methylation d mtDNA 6mA affects mitochondrial transcription, replication, and activity d The 6mA level in mtDNA is significantly elevated under hypoxic stress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
215
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(221 citation statements)
references
References 77 publications
6
215
0
Order By: Relevance
“…We note that numerous genome-wide studies did not produce an agreeable consensus DNA sequence containing N6mA from mammalian cells: sequences reported include TTTTT A GAAGC or TAC A [A/G]GA in mouse ES cells ( 9 , 10 ), [G/C] A GG[C/T] in a human genome (especially in the mitochondria) ( 11 ), TGG A TGGA in human glioblastoma ( 13 ), and CT[T/C/A] A TC in human mitochondria ( 21 ). From the face value of these studies, it seems that the sequences immediately before and after N6mA are both variable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that numerous genome-wide studies did not produce an agreeable consensus DNA sequence containing N6mA from mammalian cells: sequences reported include TTTTT A GAAGC or TAC A [A/G]GA in mouse ES cells ( 9 , 10 ), [G/C] A GG[C/T] in a human genome (especially in the mitochondria) ( 11 ), TGG A TGGA in human glioblastoma ( 13 ), and CT[T/C/A] A TC in human mitochondria ( 21 ). From the face value of these studies, it seems that the sequences immediately before and after N6mA are both variable.…”
Section: Resultsmentioning
confidence: 99%
“…Murine MettL4 was reported to be responsible for N6mA deposition in genic elements, corresponding with transcriptional silencing ( 10 ). Interestingly, recombinant human MettL4 expressed in HEK293T cells has in vitro enzymatic activity on mitochondrial D NA ( 21 ), whereas recombinant human MettL4 expressed in E. coli has R NA MTase activity ( 29 ). The former study showed that MettL4 localizes with mitochondria in all tested tissues ( 21 ) and the latter study found mainly nuclear localization of an exogenously introduced MettL4, and failed to identify appreciable levels of N6mA in mitochondrial DNA ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies revealed that the sample contamination, RNA contamination, technological limitations, and antibody non-specificity may cause serious problems in quantification and sequencing of 6mA in mammalian genomic DNA, casting doubts on the significance of 6mA in the mammalian genome (O’Brown et al, 2019 ; Douvlataniotis et al, 2020 ; Musheev et al, 2020 ). However, 6mA could be a regulatory mark in mammalian mitochondrial DNA (mtDNA) (Hao et al, 2020 ).…”
Section: Base-resolution Sequencing For Dna Modificationsmentioning
confidence: 99%
“…These studies centered on MOMP evoke a more general feature: mitochondrial DNA, somehow in agreement with its bacterial origin, is sensed not only as an extracellular, but also as an intracellular DAMP when in the cytosol. Its relatively low methylation status, and its propensity to oxidative damage, compared to nuclear DNA, seems to be critical [99]. Numerous studies have now established that mtDNA can stimulate many Pattern Recognition Receptors (PPRs), including cGAS as mentioned above but also TLR9 and inflammasomes (reviewed in [100]) and how all these can be triggered upon MOMP remains to be elucidated.…”
Section: Momp Contributes To An Inflammatory Signaling and To Immunogmentioning
confidence: 99%